2011
DOI: 10.11606/issn.2316-9079.v10i1p31-43
|View full text |Cite
|
Sign up to set email alerts
|

Cantos de anúncio e de combate de Centrolene lynchi (Anura: Centrolenidae), com notas sobre seu comportamento de combate e reprodutivo

Abstract: Advertisement and combat calls of the glass frog Centrolene lynchi (Anura: Centrolenidae), with notes on combat and reproductive behaviors. We describe the advertisement and combat calls, combat behavior, and reproductive behavior of the glass frog Centrolene lynchi, an endemic species of the cloud forests of Ecuador. The typical advertisement call consists of a tonal note and 1-3 peaked notes, each with 1-3 pulses. Variations on this advertisement call include the addition of a short note before the tonal not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…At Reserva Las Gralarias (Lucy's Creek), females place clutches of 21-24 neon green eggs on vegetation in males' territories (n = 4, mean = 22.25, SD = 1.08); most egg clutches are placed on top of large leaves or ferns above a fast-flowing stream at a height of 165-600 cm (n = 14, mean height = 313.3 cm, SD = 78.7). Dautel et al [50] suggested that males provide long-term parental care; however, a more detailed Variation: The dorsum of most examined specimens except one (KU 164695) have spicules and spiculated warts; it is possible that this variation is a result of the reproductive condition of this particular male individual. Females of Centrolene lynchi lack spicules, normal sexual dimorphism in Centrolenidae.…”
Section: Diagnosismentioning
confidence: 98%
See 2 more Smart Citations
“…At Reserva Las Gralarias (Lucy's Creek), females place clutches of 21-24 neon green eggs on vegetation in males' territories (n = 4, mean = 22.25, SD = 1.08); most egg clutches are placed on top of large leaves or ferns above a fast-flowing stream at a height of 165-600 cm (n = 14, mean height = 313.3 cm, SD = 78.7). Dautel et al [50] suggested that males provide long-term parental care; however, a more detailed Variation: The dorsum of most examined specimens except one (KU 164695) have spicules and spiculated warts; it is possible that this variation is a result of the reproductive condition of this particular male individual. Females of Centrolene lynchi lack spicules, normal sexual dimorphism in Centrolenidae.…”
Section: Diagnosismentioning
confidence: 98%
“…Frequency information was obtained through fast Fourier transformation, with a 50% window overlap (Hanning window size of 1024 and a frequency window of 43.1 Hz). The following call variables were measured: Call duration, duration between calls, number of notes per call, note duration, duration between notes, dominant frequency, first harmonic, second harmonic [49][50][51] (Table 1). A call is defined as the sound produced in a single exhalation of air.…”
Section: Taxonomy and Species Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of low amplitude pulses before the well-defined pulsed calls has not been previously reported in the advertisement call of Vitreorana uranoscopa (Barrio, 1968;Heyer et al, 1990). A similar variation has been reported in Centrolene lynchi and called pre-tonal note (Dautel et al, 2011). This temporal modification has been suggested to increase the information content of the advertisement calls of the frog Engystomops pustulosus (Ryan, 2001).…”
Section: Discussionmentioning
confidence: 57%
“…Thus, the information contained in calls determines territorial segregation, reproduction, and their fitness ( e.g. , Giasson & Haddad, 2006 ; Dautel et al, 2011 ). For most anurans, the tympanic membrane is the first structure to capture the external sound waves, transmitting acoustic vibrations to their inner ear.…”
Section: Introductionmentioning
confidence: 99%